Bilingual and Bicultural Research Teams: Unpacking the Complexities (Mary Ann Liebert, 2020)
Researchers often describe use of ?bilingual/bicultural? research teams, especially for research being conducted with marginalized communities. In this perspectives article, we argue that while increasing the diversity of research teams is imperative, using the term ?bilingual/bicultural? without further explanation is problematic. We first review the nuances of the terms bilingual and bicultural individually. Next, we describe how the terms bilingual and bicultural cannot be conflated. Finally, we provide recommendations for researchers, journals, and funding agencies.